Porcine respiratory disease complex after the introduction of H1N1/2009 influenza virus in Brazil. (14th November 2017) - Rech, R. R.; Gava, D.; Silva, M. C.; Fernandes, L. T.; Haach, V.; Ciacci‐Zanella, J. R.; Schaefer, R.
Summary: From 2009 to 2015, 74 lungs from suckling (6.8%), nursing (70.3%), fattening (20.3%) pigs and pregnant sows (2.7%) with respiratory signs from pig farms in Southern Brazil were submitted to a diagnostic laboratory for necropsy and/or histologic examination and screening for respiratory agents by RT‐qPCR, immunohistochemistry (IHC), virus isolation (VI) and subtyping for influenza A virus (IAV), IHC and nested PCR for Mycoplasma hyopneumoniae (Mhyo), PCR for porcine circovirus 2 (PCV2), RT‐qPCR for porcine reproductive and respiratory syndrome virus (PRRSV) and bacterial culture. All lung samples were positive for IAV using RT‐qPCR. Seventy‐two lungs had histologic lesions associated with acute to subacute IAV infection characterized by necrotizing bronchiolitis/bronchitis or bronchointerstitial pneumonia with lymphocytic peribronchiolitis and bronchiolar/bronchial hyperplasia, respectively. Forty‐nine lungs (66.2%) were positive by IHC for IAV nucleoprotein. The H1N1/2009 was the most common subtype and the only IAV detected in 58.1% of lungs, followed by H1N2 (9.5%) and H3N2 (6.8%). Coinfection of IAV and Mhyo was seen in 23 (31%) cases. Although 14.9% of the lungs were positive for PCV2 using PCR, no suggestive lesions of PCV2 disease were observed. Porcine reproductive and respiratory syndrome virus (PRRSV) was not detected, consistent with the PRRS‐free status of Brazil. Secondary bacterial infections (8/38) were associated with suppurative bronchopneumonia and/or pleuritis. Primary IAV infection with Mhyo coinfection was the most common agents found in porcine respiratory disease complex (PRDC) in pigs in Southern Brazil.